2022
DOI: 10.1038/s41598-022-13318-7
|View full text |Cite
|
Sign up to set email alerts
|

Theta but not beta activity is modulated by freedom of choice during action selection

Abstract: Large-scale neurophysiological markers of action competition have been almost exclusively investigated in the context of instructed choices, hence it remains unclear whether these markers also apply to free choices. This study aimed to compare the specific brain dynamics underlying instructed and free decisions. Electroencephalography (EEG) was recorded while 31 participants performed a target selection task; the choice relied either on stimulus–response mappings (instructed) or on participants’ preferences (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 74 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…Importantly, it has been suggested that analyzing RT as a marker of cognitive conflict in free-choice condition may not be reliable (Wong et al, 2017). In a recent study, the authors did not find difference in RT between easy and hard trials in a free-choice condition, while this difference was present in the instructed condition (Pierrieau et al, 2022). In another study, the authors suggested that free-choice tasks are similar random generation tasks and do not reflect a process of preference generation .…”
Section: Discussionmentioning
confidence: 92%
“…Importantly, it has been suggested that analyzing RT as a marker of cognitive conflict in free-choice condition may not be reliable (Wong et al, 2017). In a recent study, the authors did not find difference in RT between easy and hard trials in a free-choice condition, while this difference was present in the instructed condition (Pierrieau et al, 2022). In another study, the authors suggested that free-choice tasks are similar random generation tasks and do not reflect a process of preference generation .…”
Section: Discussionmentioning
confidence: 92%
“…The inconsistence between RT and behaviors in the free-choice condition in both groups could be explained by the fact that interpreting RT only as a marker of cognitive conflict in free-choice conditions may not be reliable (Naefgen et al, 2018; Pierrieau et al, 2022; Wong et al, 2017). It is important to note that different decision strategies can be employed in free-choice scenarios, which can influence RT (Vogel et al, 2018).…”
Section: Discussionmentioning
confidence: 98%